Analisis Faktor-Faktor Yang Mempengaruhi Volume Pembiayaan Berbasis Bagi Hasil Pada Bank Umum Syariah Di Indonesia - KURNIAWANTI, AGUSTINA, Dr. Zulfikar, SE, M.Si (2014)
The objective of this study is to analyze factors that influencing volume of profit and loss sharing based-financing in sharia banking in Indonesia during 2009-2013. The sample selection method is purposive sampling and obtained eleven Islamic banks are being sampled, that is Bank Syariah Mega Indonesia, Bank Syariah Mandiri, Bank Muamalat Indonesia, BRI Syariah, Bukopin Syariah, Bank Panin Syariah, Victoria Syariah, BCA Syariah, BJB Syariah, BNI Syariah, and Maybank Indonesia Syariah in 20 periods of observation. Analysis method used is SPSS, analysis technique used in this study using multiple linear regression with the purpose to obtain a comprehensive picture of the relationship between variables. While the classical assumption used this research include multicolinearity, autocorrelation test, homoskedastisitas test, and test for normality. The results show that profit and loss sharing level and also total assets have positive significant influence toward volume of profit and loss sharing based-financing, while depositors' funds and also non performing financing doesn't have significant influence.